Comparison of prosthetic mobility and balance in transfemoral amputees with bone-anchored prosthesis vs. socket prosthesis. Issue 2 (28th April 2023) - Gailey, Robert S.; Kristal, Anat; Al Muderis, Munjed; Lučarević, Jennifer; Clemens, Sheila; Applegate, E. Brooks; Isaacson, Brad M.; Pasquina, Paul F.; Symsack, Allison; Gaunaurd, Ignacio A.
Abstract : Background: The literature comparing bone-anchored prosthesis (BAP) with socket prosthesis (SP) consistently reports improvement in physical health and quality of life using primarily patient-reported outcome measures (PROMs). Objective: To determine the differences in mobility and balance using performance-based outcome measures and PROMs in people with transfemoral amputations (TFAs) fitted with BAP vs. SP. Study design: Causal comparative. Methods: Two groups of people with TFAs were recruited: one using a BAP (N = 11; mean age ± standard deviation, 44 ± 14.9 years; mean residual limb length as a percentage of the intact femur, 68% ± 15.9) and another group using a SP (N = 11; mean age ± standard deviation, 49.6 ± 16.0 years; mean residual limb length as a percentage of the intact femur, 81% ± 13.9), and completed the 10-meter walk test, component timed-up-and-go, Prosthetic Limb Users Survey of Mobility™ 12-item, and Activities-specific Balance Confidence Scale. Results: There were no statistically significant differences between the BAP and SP groups in temporal spatial gait parameters and prosthetic mobility as measured by the 10-meter walk test and component timed-up-and-go, yet large effect sizes were found for several variables. In addition, Activities-specific Balance Confidence Scale and Prosthetic Limb Users Survey of Mobility™ scores were not statistically different between the BAP and SP groups, yet a large effect sizes were found for both variables. Conclusions: This study found that people with TFA who use a BAP can demonstrate similar temporal spatial gait parameters and prosthetic mobility, as well as self-perceived balance confidence and prosthetic mobility as SP users. Therefore, suggesting that the osseointegration reconstruction surgical procedure provides an alternative option for a specific population with TFA who cannot wear nor have limitations with a SP. Future research with a larger sample and other performance-based outcome measures and PROMs of prosthetic mobility and balance would further determine the differences between the prosthetic options.